The Role of Organizer Teachers (Guru Penggerak) in Planning Differetiated Instruction in English Learning - Andi Nur Hasanah; Baso Jabu; Sahril Nur (Universitas Muhammadiyah Enrekang, 2023)
Differentiated instruction is the latest topic widely discussed in many articles. However, articles discussing differentiated instruction and its relationship with how organizer teachers (guru penggerak) plan the learning activities are rarely found. The research aims to describe the planning of differentiated instruction by Guru Penggerak in English learning. This research was conducted at a Senior High School in South Sulawesi, where the English teachers attended the guru penggerak program. The method used in this study is a case study of qualitative design. A purposive sampling technique was used to gain the sample. The subject of this research were two English teachers who had attended the education of Guru Penggerak batch 1. The research instruments were interview guidelines and documentation guidelines. The data was collected through interviews and documentation. The data analysis techniques used thematic analysis. The result shows that the English teacher who attended guru penggerak education planned differentiated instruction through diagnostic assessment and curriculum analysis. Keywords: guru penggerak, planning of differentiated instruction, English learning